2017
DOI: 10.2147/oarrr.s110585
|View full text |Cite
|
Sign up to set email alerts
|

Color duplex ultrasonography findings of temporal arteries in a case of giant cell arteritis: role in diagnosis and follow-up

Abstract: Giant cell arteritis (GCA) is a systemic autoimmune disease that affects medium- and large-sized arteries. The diagnostic gold standard is the temporal artery biopsy, but it has limited sensitivity and some difficulties in reproducibility. Color duplex ultrasonography is a noninvasive, reproducible, and inexpensive method for diagnosis of temporal arteries involvement (temporal arteritis [TA]) in GCA with high sensitivity and specificity. We present the ultrasound findings at baseline and during follow-up in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…That for distal frontal ramus was 2.5 cm (Fig. 2) [15]. Ultrasound examinations had performed by ultra-sonographers (minimum 3-years’ experience, blinded regarding physical features, clinical examinations, temporal artery biopsy examinations, and MRI examinations) of the institute.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…That for distal frontal ramus was 2.5 cm (Fig. 2) [15]. Ultrasound examinations had performed by ultra-sonographers (minimum 3-years’ experience, blinded regarding physical features, clinical examinations, temporal artery biopsy examinations, and MRI examinations) of the institute.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Several studies also showed a potential benefit of ultrasonographic follow-up in patients exhibiting the halo sign at baseline, with evidence of regression of the wall edema in most cases, once steroid treatment was initiated. [6,7,8,9]. However, there is lack of congruence between the mean time to halo disappearance, ranging from 7 days in one case report [7] to a mean of 11 weeks in a 30 patients cohort study [9], with both using the 0.3 mm threshold in defining the halo sign.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7,8,9]. However, there is lack of congruence between the mean time to halo disappearance, ranging from 7 days in one case report [7] to a mean of 11 weeks in a 30 patients cohort study [9], with both using the 0.3 mm threshold in defining the halo sign. One case report showed a negative halo sign after 2 days of treatment [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zajęta tętnica skroniowa może być wyczuwalna, tkliwa i niepodatna na ucisk. U ok. 30% chorych może wystąpić jednostronna ślepota spowodowana przez zamknięcie światła tętnicy środkowej siatkówki [19,20]. Tarcza nerwu wzrokowego może być prawidłowa, blada lub obrzęknięta, z krwotokami na powierzchni siatkówki.…”
Section: Olbrzymiokomórkowe Zapalenie Tętnicunclassified